Trypanosoma brucei gambiense-iELISA: A Promising New Test for the Post-Elimination Monitoring of Human African Trypanosomiasis. (28th August 2020) - Geerts, Manon; Van Reet, Nick; Leyten, Sander; Berghmans, Raf; Rock, Kat S; Coetzer, Theresa H T; Eyssen, Lauren E-A; Büscher, Philippe
Abstract: Background: The World Health Organization targeted Trypanosoma brucei gambiense human African trypanosomiasis ( g HAT) for elimination as a public health problem and for elimination of transmission. To measure g HAT elimination success with prevalences close to zero, highly specific diagnostics are necessary. Such a test exists in the form of an antibody-mediated complement lysis test, the trypanolysis test, but biosafety issues and technological requirements prevent its large-scale use. We developed an inhibition ELISA with high specificity and sensitivity that is applicable in regional laboratories in g HAT endemic countries. Methods: The T. b. gambiense inhibition ELISA ( g -iELISA) is based on the principle that binding of monoclonal antibodies to specific epitopes of T. b. gambiense surface glycoproteins can be inhibited by circulating antibodies of g HAT patients directed against the same epitopes. Using trypanolysis as reference test, the diagnostic accuracy of the g -iELISA was evaluated on plasma samples from 739 g HAT patients and 619 endemic controls and on dried blood spots prepared with plasma of 95 g HAT and 37 endemic controls. Results: Overall sensitivity and specificity on plasma were, respectively, 98.0% (95% CI 96.7–98.9) and 99.5% (95% CI 98.6–99.9). With dried blood spots, sensitivity was 92.6% (95% CI 85.4–97.0), and specificity was 100% (95% CI 90.5–100.0). The g -iELISA is stable for at least 8 months when stored at 2–8°C. Conclusion: The g -iELISA might largely replace trypanolysis for monitoring g HAT elimination and for postelimination surveillance. The g -iELISA kit is available for evaluation in reference laboratories in endemic countries. Abstract : The novel Trypanosoma brucei gambiense inhibition ELISA ( g -iELISA) is a high-throughput diagnostic applicable in regional laboratories for monitoring gambiense -HAT elimination. On plasma samples, sensitivity was 98.0% and specificity 99.5%, while on dried blood spots sensitivity was 92.6% and specificity 100%.